A natureza da ciência nos currículos de ciências - Estudo do currículo de Ciências Naturais do 3º ciclo do ensino básico - Sílvia Ferreira; Ana Maria Morais (Universidade do Minho, 2010)
The study analyses the extent to which the sociological message transmitted by the Official Pedagogic Discourse of the Natural Science curriculum for Portuguese middle school considers the nature of science. It is epistemologically and sociologically grounded with particular emphasis on Bernstein's theory of pedagogic discourse and Ziman's conceptualization of science construction. The study used a mixed methodology and followed a dialectical process between the theoretical and the empirical. The results show that the nature of science is, in general, present in the curriculum but the external sociological dimension of science is the only dimension with high status. This general low status attributed to the nature of science is compounded with the high absence in the curriculum of intradisciplinary relations between scientific and metascientific knowledge. The results also show that the Ministry of Education leaves implicit to teachers, even when they are present, not only the metascientific knowledge to be learned and the metascientific competences to be developed but also the intradisciplinary relations between scientific and metascientific knowledge. Differences were found between the two main parts of the curriculum - Essential Competences and Curriculum Guidelines - which indicate recontextualization processes. These results are discussed and their consequences in terms of scientific learning are explored.